1991
DOI: 10.1002/jnr.490300213
|View full text |Cite
|
Sign up to set email alerts
|

EGF enhances the survival of dopamine neurons in rat embryonic mesencephalon primary cell culture

Abstract: Epidermal growth factor (EGF) immunoreactive material has been demonstrated to be present in the basal ganglia. In this study, we investigated the effect of EGF on cells cultured from 16-day embryonic rat mesencephalon, which included dopamine neurons that project to the striatum in vivo. EGF receptors were detected in untreated cultures by [125I]-EGF binding. Treatment of the cultures with EGF resulted in up to 50-fold increases in neuronal high-affinity dopamine uptake. Scatchard analysis of uptake kinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(90 citation statements)
references
References 49 publications
1
88
0
1
Order By: Relevance
“…[54][55][56][57] Previous neurobiological studies have demonstrated that peptides from the EGF family exert neurotrophic effects on developing dopaminergic neurons in vitro and in vivo. 4,[13][14][15][16] In embryonic mesencephalon culture, EGF specifically enhances cell survival of dopamine neurons. 13 Intraventricular infusion of EGF elevates striatal innervation by dopaminergic fibers from the substantia nigra.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[54][55][56][57] Previous neurobiological studies have demonstrated that peptides from the EGF family exert neurotrophic effects on developing dopaminergic neurons in vitro and in vivo. 4,[13][14][15][16] In embryonic mesencephalon culture, EGF specifically enhances cell survival of dopamine neurons. 13 Intraventricular infusion of EGF elevates striatal innervation by dopaminergic fibers from the substantia nigra.…”
Section: Discussionmentioning
confidence: 99%
“…4,[13][14][15][16] In embryonic mesencephalon culture, EGF specifically enhances cell survival of dopamine neurons. 13 Intraventricular infusion of EGF elevates striatal innervation by dopaminergic fibers from the substantia nigra. 15 This is consistent with findings from TGF␣-null-mutant mice, which have decreased numbers of midbrain dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were scraped off the culture wells and counted by liquid scintillation spectrometry. Serotonin uptake was estimated similarly (Casper et al, 1991), using 20 nM 5-[3H]-hydroxytryptamine instead of DA. Blank values were determined in the presence of 3 jiM citalopram (Lundbeck and Co., Copenhagen, Denmark).…”
Section: Neurotransmitter Uptakementioning
confidence: 99%
“…De hecho, se demostró que actúa como un factor neurotrófico sobre neuronas cultivadas de la corteza cerebral, del telencéfalo subneocortical y del cerebelo, incrementando el crecimiento neurona1 y la supervivencia (5-7). Su acción neurotrófica sobre las neuronas dopaminérgicas se describió como un incremento de la supervivencia y de la maduración (8,9).…”
unclassified